2023
DOI: 10.3390/jcm12072543
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Anorectal Manometry in Children following Anorectal Malformation Repair: A Systematic Review

Abstract: Despite surgical correction, children with anorectal malformations may experience long-term bowel dysfunction, including fecal incontinence and/or disorders of evacuation. Anorectal manometry is the most widely used test of anorectal function. Although considerable attention has been devoted to its application in the anorectal malformation cohort, there have been few attempts to consolidate the findings obtained. This systematic review aimed to (1) synthesize and evaluate the existing data regarding anorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
0
3
0
2
Order By: Relevance
“…Although anorectal manometry is now the most widely used investigational tool for detecting abnormalities in anorectal coordination and/or anal sphincter complex dysfunction, as stated in a recent systematic review on anorectal manometry in children who have undergone ARMs repair, it remains clinically challenging to determine the definitive thresholds for sphincter dysfunction that may lead to fecal incontinence [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although anorectal manometry is now the most widely used investigational tool for detecting abnormalities in anorectal coordination and/or anal sphincter complex dysfunction, as stated in a recent systematic review on anorectal manometry in children who have undergone ARMs repair, it remains clinically challenging to determine the definitive thresholds for sphincter dysfunction that may lead to fecal incontinence [25].…”
Section: Discussionmentioning
confidence: 99%
“…According to their systematic review [25], manometric studies have been performed for the purpose of comparing different types of ARMs, evaluating operative techniques, assessing post-operative modalities, predicting bowel function, and investigating the pathophysiology and management of post-operative bowel dysfunction. Different manometric equipment, assessment protocols, and parameter definitions used in various studies have led to significant deviation in results.…”
Section: Discussionmentioning
confidence: 99%
“…Низька кишкова непрохідність може траплятися з кількома кишковими петлями. Необхідно діагностувати аномальне співвідношення прямої кишки і сигмоподібної кишки, перехідну зонузвуження прямої кишки, нерегулярні скорочення прямої кишки та затримку контрастного матеріалу на відстрочених рентгенограмах [20]. Рентгенологічна оцінка новонародженого з неперфорованим заднім проходом включає ультразвукове досліджен-ня черевної порожнини для виявлення урологічних аномалій.…”
Section: результати дослідженняunclassified
“…Атрезія прямої кишки є рідкісною анорактальною вадою розвитку, що поєднує нормально розвинений задній прохід і атретичний сегмент прямої кишки. Неможливість відходження меконію у новонародженого з нормальним наявним анусом повинна призвести до подальших клінічних та радіологічних досліджень, результати яких є специфічними Двадцятиденна дівчинка поступила з анамнезом хронічного блювання, відсутності меконію з народження та прогресуючого здуття живота [20]. При дослідженні промежини виявлено нормально розміщений задній прохід без нориці промежини.…”
Section: результати дослідженняunclassified

Anorectal developmental anomalies

Антонюк,
Пикалюк,
Слободян
et al. 2023
NCBio
“…The prevalence of FI in patients operated for ARM varies based on the severity and extent of the underlying congenital defect and the presence of other associated abnormalities, but the most relevant underlying pathophysiological mechanism is almost uniformly an abnormal anal sphincter function. A recent, large systematic review of the literature identified a hypotensive anal sphincter as the most consistent finding in children with ARM, particularly in those with more complex malformation types 39 . Impaired anal and rectal sensation also contribute to the FI in a subset of patients.…”
Section: Introductionmentioning
confidence: 99%